Designing Around People CWUAAT 2016 - Langdon, Pat; Lazar, Jonathan; Heylighen, Ann; Dong, Hua (Springer International Publishing : Imprint: Springer, 2016)
This book presents the proceedings of the 8th Cambridge Workshop on Universal Access and Assistive Technology (CWUAAT '14), incorporating the 11th Cambridge Workshop on Rehabilitation Robotics, held in Cambridge, England in March 2016. It presents novel and state-of-the-art research from an international group of leaders in the fields of universal access and assistive technology. It explores various issues including the reconciliation of usability, accessibility and inclusive design, the design of inclusive assistive and rehabilitation systems, measuring product demand and human capabilities, data mining and visualizing inclusion, legislation in inclusive design, and situational inclusive interfaces (automotive and aerospace). This book provides an invaluable resource to researchers, postgraduates, design practitioners, therapists and clinical practitioners, as well as design teachers.